2015
DOI: 10.5897/ajb2015.14833
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the kernels of Pentadesma butyracea from various growing sites of Benin and evaluation of their antioxidant pigments content

Abstract: Pentadesma butyracea Sabine (Clusiaceae) is a ligneous forest species of multipurpose uses. It is widely distributed in Africa from Guinea-Bissau to the West of the Democratic Republic of Congo. This study screened the kernel of P. butyracea on the basis of their physico-chemical properties. Six types of kernels were distinguished. The plant producing type 1 kernels (with medium length, low width and high thickness) and type 5 kernels (with high length, high width and high thickness) predominate within accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The variation in levels of fat content in plant kernels could be attributed to different factors such as environmental influences, agronomic and genetic characteristics, period of harvest, and extraction methods (Grundy et al, 2020;Honfo et al, 2014;Nahm et al, 2013). Ayegnon et al reported that the germ fraction of the P. butyracea kernel is the most oil-rich part (53.15%), followed by albumen (37.49%) (Ayegnon, Kayode, et al, 2015). The level of P. butyracea kernel oil was higher than those of most conventional oils such as soybean (18% to 22%) (Yao et al, 2020), palm fruit (20%), palm kernel (36%), cottonseed (35%), groundnut (42%) (Jahurul et al, 2022;Ladele et al, 2016), and sunflower seed (36% to 50%) (Rauf et al, 2017), but lower than that of Terminalia catappa (61.76%) (Jahurul et al, 2022;Ladele et al, 2016).…”
Section: Physicochemical and Nutritional Composition Of Pentadesma Ke...mentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in levels of fat content in plant kernels could be attributed to different factors such as environmental influences, agronomic and genetic characteristics, period of harvest, and extraction methods (Grundy et al, 2020;Honfo et al, 2014;Nahm et al, 2013). Ayegnon et al reported that the germ fraction of the P. butyracea kernel is the most oil-rich part (53.15%), followed by albumen (37.49%) (Ayegnon, Kayode, et al, 2015). The level of P. butyracea kernel oil was higher than those of most conventional oils such as soybean (18% to 22%) (Yao et al, 2020), palm fruit (20%), palm kernel (36%), cottonseed (35%), groundnut (42%) (Jahurul et al, 2022;Ladele et al, 2016), and sunflower seed (36% to 50%) (Rauf et al, 2017), but lower than that of Terminalia catappa (61.76%) (Jahurul et al, 2022;Ladele et al, 2016).…”
Section: Physicochemical and Nutritional Composition Of Pentadesma Ke...mentioning
confidence: 99%
“…Ayegnon et al. reported that the germ fraction of the P. butyracea kernel is the most oil‐rich part (53.15%), followed by albumen (37.49%) (Ayegnon, Kayode, et al., 2015 ). The level of P. butyracea kernel oil was higher than those of most conventional oils such as soybean (18% to 22%) (Yao et al., 2020 ), palm fruit (20%), palm kernel (36%), cottonseed (35%), groundnut (42%) (Jahurul et al., 2022 ; Ladele et al., 2016 ), and sunflower seed (36% to 50%) (Rauf et al., 2017 ), but lower than that of Terminalia catappa (61.76%) (Jahurul et al., 2022 ; Ladele et al., 2016 ).…”
Section: Chemical Composition Of P Butyracea Fruitmentioning
confidence: 99%